2021
DOI: 10.1186/s12970-021-00413-9
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine supplementation enhances simulated game performance of archery athletes

Abstract: Background Nicotine is beneficial to mood, arousal and cognition in humans. Due to the importance of cognitive functioning for archery athletes, we investigated the effects of nicotine supplementation on the cognitive abilities, heart rate variability (HRV), and sport performance of professional archers. Methods Eleven college archers were recruited and given 2 mg of nicotine supplementation (NIC group) and placebo (PLA group) in a crossover design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…Although nicotine has many adverse effects, its potential pharmacological effects on central nervous system (CNS) diseases has attracted attention, especially nicotine may have beneficial effects on the treatment of Parkinson's disease (PD), Alzheimer's disease (AD), schizophrenia and depression [10] . Moreover, nicotine has many pharmacological effects in the treatment of some diseases and function regulation, such as enhancing related auditory processing in humans, [11] increasing cognitive function and stimulating the sympathetic adrenergic system, [12] and having the potential for treatment of sarcoidosis [13] . This part summarized the pharmacological effects of nicotine reported in recent years in order to provide reference for further studies.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Although nicotine has many adverse effects, its potential pharmacological effects on central nervous system (CNS) diseases has attracted attention, especially nicotine may have beneficial effects on the treatment of Parkinson's disease (PD), Alzheimer's disease (AD), schizophrenia and depression [10] . Moreover, nicotine has many pharmacological effects in the treatment of some diseases and function regulation, such as enhancing related auditory processing in humans, [11] increasing cognitive function and stimulating the sympathetic adrenergic system, [12] and having the potential for treatment of sarcoidosis [13] . This part summarized the pharmacological effects of nicotine reported in recent years in order to provide reference for further studies.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Evidence indicates that chewing gum can enhance attention, in addition to promoting work performance [ 14 ]. The relationship between chewing and cognitive function was investigated through electroencephalography (EEG), and the results revealed that alpha power was increased after chewing [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The players would chew tobacco and consume nicotine simultaneously. Previous studies supported that consumption of nicotine in the form of tobacco chewing or nicotine gum is considered to benefit sports practice and performance [ 6 , 7 , 14 ]. Nicotine gum is a relatively safer sports supplementation than tobacco chewing for health conditions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of archery in Indonesia is motivated by the public's view that archery can train focus, concentration and improve one's physical fitness (Humaid, 2014;Hung et al, 2021). Archery itself is a static sport that requires good physical conditions, namely strength and endurance, especially in the upper body muscles (Fahrizqi et al, 2021;Hardi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%